Formation of mechanisms for sustainable development of industrial enterprises on the example of the power industry - V. V. Lebedev (Вестник университета)
The scientific novelty of the study consists in identifying necessary mechanisms for sustainable development of industrial enterprises. Nowadays the industry have set to create balanced growth to solve modern global challenges. It also takes measures to ensure energy security and maintains stable flows of finance and capital with stability of investment activity. The purpose of the study is to determine the formation of mechanisms for the sustainable development of industrial enterprises. Based on the results, a special System of management has been created by redesigning the process of implementing an investment project. Its boundaries can be extended to manage the full life cycle of an investment project from an idea to summarizing the project in terms of its payback and other performance indicators.